Structural analysis with mixed frequencies: monetary policy, uncertainty and gross capital flows - Emanuele Bacchiocchi; Andrea Bastianin; Alessandro Missale; Eduardo Rossi (European Commission, Joint Research Centre (JRC), 2016)
In this paper we study how monetary policy, economic uncertainty and economic policy uncertainty impact on the dynamics of gross capital inflows in the US. Particular attention is paid to the mixed frequency-nature of the economic time series involved in the analysis. A MIDAS-SVAR model is presented and estimated over the period 1988-2013. While no relation is found when using standard quarterly data, exploiting the variability present in the series within the quarter shows that the effect of a monetary policy shock is greater the longer the time lag between the month of the shock and the end of the quarter. In general, the effects of economic and policy uncertainty on US capital inflows are negative and significant. Finally, the effect of the three shocks is different when distinguishing between financial and bank capital in ows from one side, and FDI from the other.
Keywords: C32; E52; 330; Gross capital inflows; monetary policy; economic and policy uncertainty; mixed frequency variables